The Assessment of Hygiene and Sanitation Practice in "Penyetan” Food Traders In The Sunan Ampel Religious Tourism Area Surabaya - Nasyihatus Sakinah (JURNAL KESEHATAN LINGKUNGAN, 2019)
Sunan Ampel Religion Tourism area Surabaya is one of the most visited destinations for visitors and tourists that is surrounded by food traders carts, unfortunately food hygiene and sanitation practice among them is still poorly implemented that it could initiates food borne disease transmission. This study aims to analyze the personal hygiene conditions of food handlers, sanitation of merchant facilities and quality of feeders in the Sunan Ampel Religious Tourism Area, Surabaya. This research is a descriptive observational study with cross sectional design. The population in this study were 30 penyetan food traders and food samples in the form of sambal (chili paste) penyetan to be observed for the presence or absence of E. coli bacteria. The results of the study showed that the penyetan food handlers in the Sunan Ampel religious tourism area were at at age group of 20-25 years old for 14 subjects (46.67%). The subject respondents in majority are men with total of 21 subjects (70%). The education level of the respondents is high school for 10 respondents (33.33%). The highest proportion of work period is 1-5 years is for 14 respondents (46.66%). Overall, hygiene condition of the food handlers is 100% in high category. Sanitation conditions for food merchant facilities that meet the requirements are 28 stalls (93.33%). Laboratory test results found 2 samples of chili paste positive with E. Coli bacteria. This study concludes that the hygiene condition of food handlers in the Sunan Ampel Religious Tourism Area was nearly in accordance with hygiene and sanitation standard, however, further practice monitoring is required as respondents frequently did not use aprons, used jewelry and smoking while working. therefore, a risk of food contamination is still a significant threat of the area. The result of the sanitation assessment of public facilities within the area showed that 70% of them have been met with the requirement.